Identification and comparison of factors related to academic failure in medical colleges; A Bi-center, comparative study - Faiza kiran; Syed Moyn Aly; Al Shehri, Abdullah (Journal of the Pakistan Medical Association, 2021)
Objectives: The objectives of our study were to identify the student’s perceptions related to their academic failure and compare these perceptions with their nationality. Methods: A, non-interventional, bi national, comparative study was conducted in medical colleges of Pakistan and Saudi Arabia, in year 2015-2018, by taking a purposive sample of 210 students. All those who gave consent and scored less than fifty percent in their professional examinations were included. Data was analyzed using SPSS version 23. Frequencies and percentages were calculated, and Man Whitney U was applied to calculate p value. Results: According to the respondents, common reasons of failure identified were information overload (n=114,50%), difficult examination (n=101, 48%), poor teaching skills of teachers (n=82, 39%), system of education (n=75,36%) and unfair examination (n=78,37%). Eleven items in nationality group were found significant. Conclusion: Regardless of few cultural and environmental differences in factors contributing towards failure in students of different countries, the risk factors are common to all students. Moreover, most students tend to blame external factors more than internal ones. Keywords: Risk, factors, Perceived, academic, failure, students, medical, Saudi Arabia, nationality, Pakistan, perceptions